2020
DOI: 10.1111/1751-7915.13640
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic community with six Pseudomonas strains screened from garlic rhizosphere microbiome promotes plant growth

Abstract: The rhizosphere microbiome plays an important role in the growth and health of many plants, particularly for plant growth-promoting rhizobacteria (PGPR). Although the use of PGPR could improve plant production, real-world applications are still held back by low-efficiency methods of finding and using PGPR. In this study, the structure of bacterial and fungal rhizosphere communities of Jinxiang garlic under different growth periods (resume growth, bolting and maturation), soil types (loam, sandy loam and sandy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 54 publications
(58 reference statements)
3
60
0
Order By: Relevance
“…This is the first comparative analysis of this type to have been performed on arable crop residues, a matrix of major agroecological importance. By focusing on methodological aspects, we have extended a broader experimental work (Kerdraon et al, 2019b;2019c;2020), paving the way for further technical improvements. The isolation approach used here for bacteria was based on a single medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first comparative analysis of this type to have been performed on arable crop residues, a matrix of major agroecological importance. By focusing on methodological aspects, we have extended a broader experimental work (Kerdraon et al, 2019b;2019c;2020), paving the way for further technical improvements. The isolation approach used here for bacteria was based on a single medium.…”
Section: Resultsmentioning
confidence: 99%
“…Together with the high-throughput isolation, this may partly explain the greater similarity of the results obtained by the two approaches for bacterial profiles than for fungal profiles It appears to be essential to combine the two approaches if we wish to go beyond descriptive aspects and characterize the ecological function of a microbial community. The main advantage of microbial isolation is that the different strains can be preserved and then testedindividually or after the creation of synthetic communities (Großkopf and Soyer, 2014; Sergaki et al 2018) -to decipher these ecological functions and identify positive specific interactions (Durán et al, 2018;Liu et al, 2019;Zhuang et al, 2020). Conversely, metabarcoding limits the biases linked to the cultivable/non-cultivable nature of microbes in the fine characterization of communities, and dedicated statistical analyses, such as linear discriminant analysis or ecological network analysis, are complementary approaches that could be used to identify putative microbial interactions (e.g.…”
Section: Some Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteria in the stems come from the environmental soil, air, air or water, which are enriched by microorganisms (Doju et al 2018). This may explain the greater richness in the roots compared to the stems (Zhuang et al 2020). Over time, endophytic bacteria from the roots can migrate or be transported to the upper parts of plants (Lamo et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Genus Pseudomonas was proved to be a group of plant growth promoting rhizobacteria (PGPR) [36][37]. For instance, Pseudomonas was found to be a key PGPR in the rhizosphere of garlic regardless of growth periods, soil types and agricultural practices, the constructed six Pseudomonas strains displayed strong plant growth promoting effects [38]. These results indicated that the stronger growth characteristics of A. sinensis in Gansu group may be related to the increased abundance of these antagonistic microorganisms in the rhizosphere.…”
Section: Effect Of Soil Type On the Composition Of Rhizosphere Bactermentioning
confidence: 97%